Occurrence and diversity of Listeria monocytogenes in Portuguese dairy farms - Nunes, Bárbara (2024)
Listeria monocytogenes is a pathogenic microorganism that causes listeriosis, an infection that usually occurs after consumption of contaminated food and is considered particularly dangerous due to its ability to grow and multiply under adverse conditions. In recent years, there has been an increase in the consumption of unprocessed products, such as raw milk and dairy products, by people of all ages, including those with compromised immune systems, which could lead to an increase in foodborne illness. Ruminants play a very important role in the persistence and transmission of L. monocytogenes through a continuous oral-faecal cycle. Therefore, farms are considered a reservoir of this microorganism and are involved in the transmission from animals to humans. In this study, samples of faeces, milk, water, silage, feed and teat cups swabs were collected from 8 farms to assess the distribution of the pathogen in the farm environment. Milk samples were also collected from 100 dairy farms to assess the risk associated with the consumption of raw milk. Detection was performed by real-time PCR, while preparation, enrichment and confirmation were performed according to ISO 11290-1, (2017). The prevalence in water was 8.3%, in faeces 12.5% and in feed 12.0%, while in the other samples the microorganism was not detected. It was also observed that this microorganism was more abundant in spring months. The eight isolates were serotyped by real-time PCR and the most frequent serogroup was IVb with 5 isolates (2 of which were IVb-v1) and the remaining 3 were IIb. Two of the clonal complexes (CCs) identified were shared by two isolates (CC 213 and CC 217), the remaining CCs identified (CC 392, CC 554, CC 489, CC 224 and CC 183) were not identified in more than one isolate. This study contributed to a better understanding of the ecology of L. monocytogenes in dairy farms, showing that most of the clones found in food were not present in this environment and that genes coding for disinfectants and heavy metals were not detected.